Particle deposition in a child respiratory tract model: in vivo regional deposition of fine and ultrafine aerosols in baboons. - Iolanda Albuquerque-Silva (Public Library of Science (PLoS), 2014)
To relate exposure to adverse health effects, it is necessary to know where particles in the submicron range deposit in the respiratory tract. The possibly higher vulnerability of children requires specific inhalation studies. However, radio-aerosol deposition experiments involving children are rare because of ethical restrictions related to radiation exposure. Thus, an in vivo study was conducted using three baboons as a child respiratory tract model to assess regional deposition patterns (thoracic region vs. extrathoracic region) of radioactive polydisperse aerosols ([d16-d84], equal to [0.15 µm-0.5 µm], [0.25 µm-1 µm], or [1 µm-9 µm]). Results clearly demonstrated that aerosol deposition within the thoracic region and the extrathoraic region varied substantially according to particle size. High deposition in the extrathoracic region was observed for the [1 µm-9 µm] aerosol (72% ± 17%). The [0.15 µm-0.5 µm] aerosol was associated almost exclusively with thoracic region deposition (84% ± 4%). Airborne particles in the range of [0.25 µm-1 µm] showed an intermediate deposition pattern, with 49% ± 8% in the extrathoracic region and 51% ± 8% in the thoracic region. Finally, comparison of baboon and human inhalation experiments for the [1 µm-9 µm] aerosol showed similar regional deposition, leading to the conclusion that regional deposition is species-independent for this airborne particle sizes.